P214 Long-term outcomes of paediatric patients admitted for Acute Severe Colitis - a multicentre study from the paediatric IBD porto group of ESPGHAN. (16th January 2018) - Krauthammer, A; Tzivinikos, C; Assa, A; Miele, E; Strisciuglio, C; Ledder, O; Shamasneh, I; Serban, D; Hojsak, I; Malham, M; de Meij, T; Dipasquale, V; et al.
Abstract: Background: Nearly 30% of paediatric ulcerative colitis (UC) patients develop acute severe colitis (ASC) flares requiring admission. Colectomy rates in these cases vary in different studies, ranging between 10–30%. However, most of these studies have been conducted in the pre-biologic era, and have provided follow-up only up to a year after admission. Our aim was to define the long-term outcomes of paediatric UC patients admitted with ASC. Methods: This was a multicentre retrospective study from centres affiliated with the Paediatric IBD Porto Group of ESPGHAN. Data on paediatric UC patients admitted during 2009–2011 for ASC flares were collected at 4 different time-points: admission and 1, 3 and 5 years following admission. The primary outcome was to define colectomy rates at each time point. Results: A total of 96 UC patients that were followed for 5 years after an ASC admission were included in this study. The mean age of the patients at diagnosis of UC was 12.3 years; 79% of them presented with extensive disease or pan-colitis. The mean age at ASC admission was 13.2 years. Twenty-four percent of the patients were considered steroid non-responders, and 8 patients (8.3%) underwent colectomy during the initial admission. Overall, colectomy rates at 1, 3 and 5 years post-ASC admission were 27%, 32% and 34%, respectively. Interestingly, steroid-responsiveness during initial ASC admission did not predict colectomy-free survival rates at 1, 3 and 5 years. Conclusions: High colectomy rates were reported in our cohort, mainly in the first year following ASC admission. Additional long-term prospective studies are required to determine whether therapeutic drug monitoring and increased infliximab dosing during ASC flares reduce surgery rates in these patients.